2018
DOI: 10.5897/ajar2018.13612
|View full text |Cite
|
Sign up to set email alerts
|

Screening of allelopathic activity of common weed species occurring in agricultural fields

Abstract: The investigation of allelopathic effects of different plant species is important to prevent serious crop losses that would arise. The usage of such materials as mulch, cover crops or residues will be useful to implement in integrated weed management strategies of agricultural fields. Therefore, this study was conducted to screen the allelopathic effect of selected plant species using seedlings growth of lettuce (Lactuca sativa L.) as an indicator. The sandwich method was used and 20 mg of dried plant material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Indeed, several studies have reported both H. suaveolens and U. lobata to exhibit allelopathic effects on other neighbouring plants in their invaded habitats ( Islam and Kato-Noguchi 2013 ; Poornima et al . 2015 ; Kaliyadasa and Jayasinghe 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported both H. suaveolens and U. lobata to exhibit allelopathic effects on other neighbouring plants in their invaded habitats ( Islam and Kato-Noguchi 2013 ; Poornima et al . 2015 ; Kaliyadasa and Jayasinghe 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is mostly utilized for the characterization of plants (Misra and Srivastava 2016;Singh, 2016;Liu et al, 2017). This method is also utilized for the characterization of pathogens (Martinelli et al, 2015;Franco-Duarte et al, 2019) and insects (Braga et al, 2013;Snart et al, 2015) and weeds (Dahiya et al, 2017;Giri and Dhanalakshmi, 2018;Kaliyadasa and Jayasinghe, 2018).…”
Section: Chemotaxonomy and Chemosystematicsmentioning
confidence: 99%
“…Several researchers have delineated allelochemicals as natural pesticides. Allelochemicals generally have a mode of action all completely different from artificial herbicides, being further merely and quickly degradable due to a shorter half-life, with relatively fewer group substituents and no unnatural ring structures (Dayan et al, 2009;Kaliyadasa and Jayasinghe, 2018).…”
mentioning
confidence: 99%
“…Phytochemicals have low or no toxicity to animals and useful insects, possess an array of activity with variable and various sites of action and have a relatively high degradation rate (Regnault et al, 2004;Kaliyadasa and Jayasinghe, 2018). Allelochemicals could influence very important physiological processes like respiration, chemical action, biological process and elongation, membrane liquidness, macromolecule biogenesis and activity of the many enzymes, and should additionally have an effect on tissue water standing (Cloyd, 2004;Papadopoulos et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation